2017
DOI: 10.3389/fnhum.2016.00695
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar tDCS: A Novel Approach to Augment Language Treatment Post-stroke

Abstract: People with post-stroke aphasia may have some degree of chronic deficit for which current rehabilitative treatments are variably effective. Accumulating evidence suggests that transcranial direct current stimulation (tDCS) may be useful for enhancing the effects of behavioral aphasia treatment. However, it remains unclear which brain regions should be stimulated to optimize effects on language recovery. Here, we report on the therapeutic potential of right cerebellar tDCS in augmenting language recovery in SMY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 42 publications
2
42
1
1
Order By: Relevance
“…A recent systematic literature review including five meta-analyses and 48 studies found some evidence in the literature that tDCS could be effective for poststroke aphasia rehabilitation at the chronic stages, but there is still a lot of variability between studies (Biou et al, 2019). The nature of the task, the stimulation site, the intensity and duration of the stimulation greatly differed from one study to the other (Baker et al, 2010;Branscheidt et al, 2018;Cherney et al, 2013;Ewa et al, 2013;Jung et al, 2011;Lee et al, 2013;Manenti et al, 2015;Marangolo et al, 2014Marangolo et al, , 2017Sebastian et al, 2016;Vestito et al, 2014;Vines et al, 2011;Wu et al, 2015;You et al, 2011). Nevertheless, there is a consensus in the existing literature on the need of combining stimulation with speech-language therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic literature review including five meta-analyses and 48 studies found some evidence in the literature that tDCS could be effective for poststroke aphasia rehabilitation at the chronic stages, but there is still a lot of variability between studies (Biou et al, 2019). The nature of the task, the stimulation site, the intensity and duration of the stimulation greatly differed from one study to the other (Baker et al, 2010;Branscheidt et al, 2018;Cherney et al, 2013;Ewa et al, 2013;Jung et al, 2011;Lee et al, 2013;Manenti et al, 2015;Marangolo et al, 2014Marangolo et al, , 2017Sebastian et al, 2016;Vestito et al, 2014;Vines et al, 2011;Wu et al, 2015;You et al, 2011). Nevertheless, there is a consensus in the existing literature on the need of combining stimulation with speech-language therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 19 studies described the use of a stimulation at 1 mA and 22 at 2 mA. A stimulation intensity of 2 mA during 20 min repeated for 10 to 30 sessions has been a frequently used stimulation paradigm (Branscheidt et al, 2018;Marangolo et al, 2013b;Meinzer et al, 2016;Sebastian et al, 2016;Volpato et al, 2013;Wu et al, 2015). The electrode's placement differs from one study to another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By targeting the cerebellum, the same protocol can be used in different patient populations, leading to a better patient stratification. A recent study by Sebastian et al [38] showed that cerebellar stimulation indeed improves cognitive functions after stroke. The authors applied tDCS over the right cerebellar hemisphere in order to enhance the effects of behavioral aphasia therapy (spelling to dictation) in a patient who suffered anarthria and aphasia after a large bilateral stroke.…”
Section: Introductionmentioning
confidence: 99%
“…As detailed above, cerebellar stimulation can modulate a wide range of behaviours in healthy subjects, and so has the potential to influence symptoms suffered by stroke patients. Certainly, a few small scale studies have shown success in improving post-stroke symptoms, such as greater recovery of language and spelling abilities with multiple sessions of cerebellar tDCS combined with spelling therapy compared to therapy alone [77].…”
Section: Cerebral Strokementioning
confidence: 99%